Barium sulfate micro- and nanoparticles as bioinert reference material in particle toxicology. Issue 10 (25th November 2016) - Loza, Kateryna; Föhring, Isabell; Bünger, Jürgen; Westphal, Götz A.; Köller, Manfred; Epple, Matthias; Sengstock, Christina
Abstract: The inhalation of particles and their exposure to the bronchi and alveoli constitute a major public health risk. Chemical as well as particle-related properties are important factors for the biological response but are difficult to separate from each other. Barium sulfate is a completely inert chemical compound, therefore it is ideally suited to separate these two factors. The biological response of rat alveolar macrophages (NR8383) was analyzed after exposure to barium sulfate particles with three different diameters (40 nm, 270 nm, and 1.3 μm, respectively) for 24 h in vitro (particle concentrations from 12.5 to 200 μg mL − 1 ). The particles were colloidally stabilized as well as fluorescently-labeled by carboxymethylcellulose, conjugated with 6-aminofluorescein. All kinds of barium sulfate particles were efficiently taken up by NR8383 cells and found inside endo-lysosomes, but never in the cell nucleus. Neither an inflammatory nor a cytotoxic response was detected by the ability of dHL-60 and NR8383 cells to migrate towards a chemotactic gradient (conditioned media of NR8383 cells) and by the release of inflammatory mediators (CCL2, TNF-α, IL-6). The particles neither caused apoptosis (up to 200 μg mL − 1 ) nor necrosis (up to 100 μg mL − 1 ). As only adverse reaction, necrosis was found at a concentration of 200 μg mL − 1 of the largest barium sulfate particles (1.3 μm). Barium sulfate particles are ideally suited as bioinert control to study size-dependent effects such as uptake mechanisms of intracellular distributions of pure particles, especially in nanotoxicology.